Kajian Kesan Pencemaran Bunyi Kenderaan Bermotor Di Kawasan Parit Buntar - Ab. Ghani, Anuar (Universiti Sains Malaysia, 2006)
Road traffic noise has become an important factor in the development of any society, in terms of living comfort and also from an economic point of view. Noise generated by road traffic should be addressed by the different government agencies. The exposure of individuals to road traffic noise can cause health problems, is very disturbing or annoying to individuals an under certain condition can also effect the work efficiency and general quality of life for the society. These study were carried out in four days where two days allotted for Simpang Empat and another two days for Simpang Lima. Three type of monitoring was carried out in this study, firstly to get noise level values in Leq, secondly to determine the composition and lastly vehicles speed during peek times at morning (7.00 – 9.00 am), mid-days (12.00 – 2.00 pm), afternoon (4.00 – 6.00 pm) and also evening (8.00 – 10.00 pm) were determined. Before the study were carried out, the questionnaires were distribute to the residents of Simpang Empat and Simpang Lima. The result from collected data showed that for a residential place the noise levels were high greater than the stimulated compliancy of 60 dBA for residential area for day time and 55 dBA for night. The range of Leq level at Simpang Empat is between 79.67 dBA – 86.07 dBA and whilst for Simpang Lima, the range is between 78.81 dBA – 87.06 dBA. From questionnaires, the road traffic noise was highest in the afternoon by 60 % of local respondents for Simpang Empat and 55.10 % for Simpang Lima. Heavy transport such as lorries and buses were the main contributor for road traffic noise.